Segmenting the fine dining restaurant market via consumers' purchasing orientation / Salim Abdul Talib ... [et al.] - Abdul Talib, Salim; Hashim, Rahmat; Kumar, Mukesh; Chinna, Karuthan (Faculty of Business and Management ; UiTM Press, 2009)
The hospitality businesses have increasingly adopted a marketing focus in order to thrive in a very competitive business environment. A key element of the marketing concept is that of market segmentation, primarily based on an understanding of the social, economic and psychological location of the consumer. Market segmentation can be considered as one of the cornerstones of marketing management. In the present day scenario of intense competition, organization can prosper through the development of offers for specific market segments as a result of good market segmentation strategy. This paper presents the result and implications of segmenting the fine dining restaurant market using consumer's purchasing orientation.